2020
DOI: 10.3389/fagro.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

A Gender Perspective on Pest and Disease Management From the Cases of Roots, Tubers and Bananas in Asia and Sub-Saharan Africa

Abstract: Considering gender in research on pests and diseases is increasingly important as it facilitates development of more efficient approaches to increasing the adoption of crop protection technologies and practices by women and men farmers according to their roles, knowledge, and capacities. However, this task is often assigned to social scientists in isolation from agronomists. Meanwhile, agronomists often struggle to understand how taking a gender perspective could enrich their research. Drawing on a number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Women play significant roles in pest management in some regions, such as obtaining and planting healthy seed/planting materials, identifying pest symptoms, (Iradukunda et al, 2019;Nkengla-Asi et al, 2019;Upadhyay et al, 2018) and participating in crop protection activities, such as pesticide application (Schreinemacheres et al, 2017). However, the lack of gender and social perspectives in plant health surveillance, technology development, access to extension services, and impact evaluation has been one of the major impediments in improving the adoption of IPM strategies (Kawarazuka et al, 2020;Tambo et al, 2021;Terefe, 2020).…”
Section: Gender Issues and Disciplinary Gap Between Social And Biophy...mentioning
confidence: 99%
“…Women play significant roles in pest management in some regions, such as obtaining and planting healthy seed/planting materials, identifying pest symptoms, (Iradukunda et al, 2019;Nkengla-Asi et al, 2019;Upadhyay et al, 2018) and participating in crop protection activities, such as pesticide application (Schreinemacheres et al, 2017). However, the lack of gender and social perspectives in plant health surveillance, technology development, access to extension services, and impact evaluation has been one of the major impediments in improving the adoption of IPM strategies (Kawarazuka et al, 2020;Tambo et al, 2021;Terefe, 2020).…”
Section: Gender Issues and Disciplinary Gap Between Social And Biophy...mentioning
confidence: 99%
“…Gender-sensitive training and extension services are critical to address gendered pest management challenges. According to Kawarazuka et al (2020), women's failure to spray is due to limited financial resources, knowledge, and access to information (Kawarazuka et al 2020). Further, females and males were found to adopt different pest control methods (Kawarazuka et al 2020); hence, there is a need to assess and consider gendered pest control methods.…”
Section: Gendermentioning
confidence: 99%
“…According to Kawarazuka et al (2020), women's failure to spray is due to limited financial resources, knowledge, and access to information (Kawarazuka et al 2020). Further, females and males were found to adopt different pest control methods (Kawarazuka et al 2020); hence, there is a need to assess and consider gendered pest control methods. In a study in KwaZulu-Natal, South Africa, poor capital asset endowments, socio-economic factors, livelihood strategies, and transforming structures and processes were blamed for challenging investment opportunities of female farmers in rural communities (Sharaunga and Mudhara 2021).…”
Section: Gendermentioning
confidence: 99%
“…However, Iradukunda et al (2019) observed that labor constraints of women in female-led households limits their adoption of SDSR practices, and gender norms played a role in Burundi. For instance, norms that prescribe certain managerial tasks like digging and cutting the stems to be performed by men only (Rietveld and Farnworth 2018a, b;Kawarazuka et al 2020) also affect adoption of control practices among women. Such norms can affect the adoption of both CDMU and SDSR.…”
Section: Reflections On Adoption Of Cdmu and Sdsrmentioning
confidence: 99%